Poseidon - Russell, Kurt.; Lucas, Josh.; Dreyfuss, Richard; Barrett, Jacinda; Rossum, Emmy, 1986-; Vogel, Mike.; Maestro, M*ia.; Bennett, Jimmy, 1996-; Fleiss, Mike.; Goldsman, Akiva; Henderson, Duncan; Petersen, Wolfgang; et al. (Burbank, CA : Warner Home Video, 2006)
Over 2,000 passengers and crew are celebrating New Year's Eve aboard the luxury cruise ship Poseidon. Without warning, a rogue wave hundreds of feet high, slams into the ship and rolls it upside down. Several hundred passengers remain alive in the ballroom. Realizing their only hope of rescue lies at the surface of the water, a handful of survivors, led by Dylan and Robert start to make their way past falling debris and flash fires.
DVD, region 1, widescreen presentation; Dolby Digital.
English or French dialogue, English, French or Spanish subtitles; closed-captioned.
Kurt Russell, Josh Lucas, Richard Dreyfuss, Jacinda Barrett, Emmy Rossum, Mike Vogel, Mia Maestro, Jimmy Bennett, Andre Braugher.
Director of photography, John Seale ; editor, Peter Honess ; music, Klaus Badelt ; costume designer, Erica Edell Phillips ; production designer, William Sandell.
Based on the novel by Paul Gallico and the motion picture "The Poseidon adventure."
MPAA rating: PG-13; for intense prolonged sequences of disaster and peril.
Keywords: Survival after airplane accidents, shipwrecks, etc. -- Drama; Feature films; Disaster films; Video recordings for the hearing impaired